Insurance warranties in South Africa: consideration of reform of the law on insurance warranties in South Africa and why there is a need for such reform - Deonandan, Nirvana (Department of Commercial Law, 2020)
Aim The overall aim of this dissertation is to consider reform of warranties in the area of insurance law in South Africa. In considering the main aim of this dissertation, the current law relating to insurance warranties in South Africa and other jurisdictions will be analysed in order to demonstrate why the South African position is unsatisfactory in its current form and therefore in need of reform as well as ideas on how the current law can be reformed. Thesis It will be argued that the South African law on insurance warranties is in need of reform to address unsatisfactory aspects of it indicated in recent judgments and by academic commentators and that such reform should, in broad terms, take account of consumerism and eliminate the harsh and unfair effects associated with the interpretation and implementation of warranties.